PENGARUH KELENGKAPAN PRODUK, KUALITAS PRODUK, PERSEPSI HARGA DAN CITRA TOKO TERHADAP KEPUTUSAN PEMBELIAN. ( Studi Kasus di Toko Basmallah Kota Semarang ) - Azzahra Ardewita Rissema, 15.05.51.0305; Maskur, Ali (Students' Journal of Economic and Management, 2019)
This study examines the effect of product completeness, product quality,price perception and store image on purchasing decision (case study at Semarang Basmallah Shop). The population in this study were consumers who had made purchase at the Basmallah Shop. Sampling technique with non probability sampling. This study uses a questionnaire as a data collection tool. Data analysis using multiple linear regression. The results of the study show that the product completeness variables have a significant positive effect on purchasing decision, product quality have no significant positive effect on purchasing decision, price perception have a significant positive effect on purchasing decision and store image have no significant positive effect on purchasing decision.